2015
DOI: 10.1152/physiolgenomics.00028.2015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gene signatures regulated by carvedilol in mouse heart

Abstract: Chronic treatment with the β-blocker carvedilol has been shown to reduce established maladaptive left ventricle (LV) hypertrophy and to improve LV function in experimental heart failure. However, the detailed mechanisms by which carvedilol improves LV failure are incompletely understood. We previously showed that carvedilol is a β-arrestin-biased β1-adrenergic receptor ligand, which activates cellular pathways in the heart independent of G protein-mediated second messenger signaling. More recently, we have dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We were not able to compare our results with other studies, because population based gene expression studies for substances have not been published yet. The only study that had analysed the effect of carvedilol on gene expression was for heart tissue in mice [ 32 ]. There was no overlap between the genes found in this study and the genes identified by us.…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to compare our results with other studies, because population based gene expression studies for substances have not been published yet. The only study that had analysed the effect of carvedilol on gene expression was for heart tissue in mice [ 32 ]. There was no overlap between the genes found in this study and the genes identified by us.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our group also showed that 7-day infusion of carvedilol induced a unique gene signature on multiple genes related to cardiac disease. Genes upregulated by carvedilol included those encoding proteins in the tight junctions, malaria and viral myocarditis pathway, while downregulated genes were those encoding proteins in the glycosaminoglycan biosynthesis and arrhythmogenic right ventricular cardiomyopathy (Teoh et al ., 2015). These findings make us speculate that carvedilol-responsive miRs can regulate the expression of various detrimental genes to confer cardioprotection (Fig.…”
Section: Biased Signaling On Selected Gpcrsmentioning
confidence: 99%
“…As suggested by the abovementioned studies, detailed mRNA network and pathway analyses can provide substantial insight into the effects of various stimuli on the heart. Such approaches are being used to better understand the beneficial effect of carvedilol treatment, albeit further studies in diseased hearts treated with carvedilol may be required [43]. Meta-analyses of archived RNA-sequencing datasets also promise to uncover similarities and differences between forms of stress-induced cardiac disease, exercise and genetic models, offering mechanistic insight together with suggestions for appropriate therapies [44 & ].…”
Section: Animal Modelsmentioning
confidence: 99%